Donald Trump's Speech: Understanding the U.S. Explicit and Implicit Agendas on Iran and the Muslim World - Lalu Isnaeni Rahman; Moh Fauzi Bafadal (Linguistics and ELT Journal, 2021)
The United States' war on terror effort, which began after the devastating assaults on the World Trade Center (WTC) and the Pentagon on September 11, 2001, has lasted until now. Even under Trump's presidency, U.S. foreign policy toward the Muslim world, particularly in the Middle East, has had little impact on global political stability. The latest tensions between the U.S. and Iran have proved that the "war" is still ongoing. This study aimed to analyze Donald Trump's speech concerning all of his statements referred to Iran's nuclear weapons and the related issues in the Islamic world. It also sought to investigate Donald Trump's explicit/stated and implicit/unstated agenda on Iran and the Islamic world. This research engaged with Qualitative Case Study as its framework and NVIVO Pro 12 application (Computer-Assisted Analysis) for its linguistic inquiry. As long as the United States' foreign policy toward the Muslim world stays intact, Iran will not be allowed to develop nuclear weapons, and neither will all Islamic countries. The term "terrorist" was a great strategy for reason to interfere in a country to carry out its main agenda.